Decision support for trucking vendor selection at PT. Ricakusuma Lestari Abadi Based on the SAW method - Indriyanti, Zahra Kiky Dwi; Sumanto, Sumanto (Institute of Computer Science (IOCS), 2025)
PT. Ricakusuma Lestari Abadi is a company engaged in freight forwarding services, distributing goods both domestically and internationally. In the shipping process, the company heavily relies on third-party trucking services. However, the selection process for trucking vendors has so far been conducted manually, without standardized evaluation criteria, which risks leading to subjective and inefficient decisions. Therefore, this study aims to develop a decision support system to select the best trucking vendor using the Simple Additive Weighting (SAW) method. The SAW method is used because it provides objective evaluation results based on the weighting of five main criteria: service quality (40%), cost (25%), vehicle condition (15%), vendor location (10%), and fleet availability (10%) (Alamsyah et al., 2021; Gunawan et al., 2023; Wibowo & Azizah, 2022). This research adopts a quantitative approach through observation, interviews, and literature study. The collected data were used to calculate the scores of seven trucking vendor alternatives. The results show that Johan Putra Perkasa scored the highest with a value of 0.80 and is recommended as the best vendor. Kumala ranked second with a score of 0.75, followed by Global Sukses Transportama with a score of 0.72. The developed system was implemented as a web-based application using PHP and MySQL to facilitate a more efficient, faster, and standardized vendor selection process (Lim & Silalahi, 2023).